Penentuan Sebaran Situs Purbakala Candi Tandihat I Menggunakan Metode Geolistrik di Desa Tandihat, Kabupaten Padang Lawas - Pasaribu, Prastika Ayu; Kadri, Muhammad (Universitas Negeri Medan, 2018)
Archaeological Site of Candi Tandihat I is one of the relics of the time of Hindu-Buddhist influence in Indonesia which has been in the form of ruins of biaro made of brick and mounds of soil overgrown with grass. Geoelectric and geomagnetic surveys are carried out as subsurface detection which aims to determine the distribution of the constituent rocks of the site based on resistivityvalue. Geoelectric research results obtained resistivity values of 24.1 - 583 Ωm, which is at a depth of 6.76 - 26.2 m with a distance of 15 - 65 m and 85 - 125 m interpreted as an alluvium layer consisting of silt - clay and sandy clay and sand which is a layer of rock composing sites. Based on the results of the interpretation, it can be seen that the subsurface main layer of the study area is alluvium which consists of clay, sandy clay and sand. [DETERMINATION OF THE ARCHEOLOGICAL SITE DISTRIBUTION OF TANDIHAT I TEMPLE USING GEOELECTRIC METHOD IN TANDIHAT VILLAGE, PADANG LAWAS REGENCY] (J. Sains Indon., 42(1): 7-11, 2018)Keywords:Geoelectric Method, Geomagnetic Method, Resistivity, Susceptibility, Archaeological Site